New Approach in the Energy Analysis of an NH3-NaSCN Single Effect Absorption Machine (SEAM) with a Counter-Current Coaxial Tubes Internal Heat Exchanger (3CT-IHE) - Mayi, O.T. Sosso; Njock, J.P.; Ndame, M.K. (Journal of Basic & Applied Sciences, 2021)
Energy analysis provides the ability to assess performance and determine the size of equipment in a system. However, precisely integrating the thermal behavior of the component equipment makes it possible to better assess the performance of the system. This work highlights the influence of the thermal behavior of a 3CT-IHE on the performance and size of the equipment of SEAM with NH3-NaSCN as a working fluid. Based on equations of conservation balances of mass, species and energy, the energy analysis made showed that depending on the magnitude of the heat flows of the weak and strong solutions involved in the heat exchange at the level of the 3CT-IHE, there are different temperature ranges for which the weak solution or the strong solution governs the heat transfer, thus giving rise to the notions of “thermal heating efficiency” and “thermal cooling efficiency” respectively. The results obtained were compared with those of Sun. This new approach has demonstrated better performance of the SEAM for the same operating conditions. It has also been shown that it is possible to increase the temperature of the generator above 90 °C without resorting to another working fluid and that in the case of subjecting NH3-NaSCN to supercritical conditions in temperature at the generator; it is possible to obtain a machine COP greater than 1 and an even smaller pump size.